Can we reduce conduction disturbances following transcatheter aortic valve replacement?. (2nd April 2020) - Alperi Garcia, Alberto; Muntané-Carol, Guillem; Junquera, Lucia; del Val, David; Faroux, Laurent; Philippon, François; Rodés-Cabau, Josep
ABSTRACT: Introduction : Transcatheter aortic valve replacement (TAVR) has been demonstrated to be a good alternative to surgery for treating severe aortic stenosis (AS) across the whole range of surgical risk patients. Whereas most periprocedural TAVR complications have significantly decreased over time, conduction disturbances remain high. Approaches to decrease this shortcoming are under continuous investigation. Areas covered : Overview of the actual evidence regarding conduction disturbances in the TAVR setting, focusing on modifiable factors. PubMed and Embase databases were used for literature search. Expert opinion : Several factors have been associated with an increased risk of conduction disturbances post-TAVR, and some of them may be modifiable. While some transcatheter valve systems have been associated with higher rates of conduction disturbances, additional randomized data are needed to draw definite conclusions about newer generation transcatheter valve systems. Nowadays, good hemodynamic valve function can be obtained without excessive valve oversizing, which has been associated with an increased risk of conduction disturbances in some studies. Also, contemporary data regarding valve implantation depth and new anatomical landmarks such as membranous septum length have provided valuable insights for procedural planning. Finally, homogenization of the management of conduction abnormalities post-TAVR should be emphasized to allow a better understanding and generalization of available evidence.